Edukasi Covid-19 Pada Anak Usia Dini - Kurniawaty, Yuni (Universitas Nusantara PGRI Kediri, 2021)
Since the start of the learning year of this strange semester, all the learning processes have been taking place online because they are in a Covid-19 pandemic situation. During the 2019 coronavirus disease pandemic (COVID-19), which is currently occurring around the world. The boredom of children who are always active at home and very limited often causes them not to do the activities recommended by the government. The proposed solutions provide information about Covid-19 in early childhood by providing education for Covid-19 via an online zoom. The development of web-based evaluations of school health promotion programs has been shown to be effective and is not inferior to face-to-face. This activity lasts one hour from 07:30 to 08:30 WIB. There are still many who do not know about Covid-19, for example the Covid-19 stands, why children have to stay at home, why cannot children go to school. The questions they raised showed that they still do not understand Covid-19. After explaining that children could answer several questions, for example length of Covid-19, signs of Covid-19, what should children do now, why should they wash their hands, wear a mask and stand away from other people. They answer the questions well.